Pemetaan Lokasi Penjualan Pupuk dan Obat-Obatan Pertanian di Kabupaten Sumbawa Berbasis GIS (Geographic Information System) - Amri Muliawan Nur; Aris Sudianto; Salmiah Salmiah; Suhartini Suhartini (Infotek: Jurnal Informatika dan Teknologi, 2022)
Most of the residents of Sumbawa Regency live in rural areas with a livelihood as farmers. In agriculture, of course, farmers need the availability of fertilizers and agricultural medicines. Fertilizers and agricultural drugs have many benefits for farmers, one of which is to stimulate plant growth and to prevent pests on plants. This is done to increase the productivity of agricultural products. However, the existence of shops selling fertilizers and medicines spread across Sumbawa, especially in several sub-districts in Sumbawa Regency, makes farmers and the general public who do not know the area have difficulty finding information on the location of the sales shop. This study aims to produce a Web-based Geographic Information System by displaying a map visualization containing the location of shops selling agricultural fertilizers and medicines spread across Sumbawa Regency. In making this system using the programming language PHP and MySQL. The use of this system is expected to help the general public as well as local farmers who do not know the area in finding the location of shops selling agricultural fertilizers and medicines. This information system contains the address mapping of fertilizer and agricultural drug stores. The research was conducted in Sumbawa Regency. The results of this study are that the public can obtain information via smartphones, assist farmers and the general public in finding the location of sales stores. In addition, to shorten the time for farmers to find locations for selling agricultural fertilizers and medicines in the Sumbawa Regency area